Modified 5-aminolevulinic acid photodynamic therapy suppresses cutaneous squamous cell carcinoma through blocking Akt/mTOR-mediated autophagic flux - Zeng, Qingyu; Liu, Jia; Yan, Yu; Zhang, Guolong; Wang, Periru; Zhang, Haiyan; Liu, Xiaojing; Zhang, Linglin; Wang, Xiuli (Frontiers in Pharmacology, 2023)
Background: We previously found that modified 5-aminolevulinic acid photodynamic therapy (M-PDT) is painless and effective in cutaneous squamous cell carcinoma (cSCC) treatment, however, the regulatory mechanism of M-PDT in cSCC is still unclear. Objective: To clarify the effect and relevant regulatory mechanism of M-PDT in cSCC. Methods: The cSCC apoptosis was examined by flow cytometry, TUNEL staining and Cleaved-caspase-3 immunofluorescence, respectively. The autophagy-related characterization was detected by monodansylcadaverine (MDC) staining, transmission electron microscopy (TEM), GFP-LC3B autophagic vacuoles localization and mRFP-EGFP tandem fluorescence-tagged LC3B construct, respectively. The expression of autophagy-related proteins and Akt/mTOR signaling molecules were examined by western blot. ROS generation was measured by DCFH-DA probe. Results: We found that M-PDT induced cSCC apoptosis in a dose-dependent manner, and this result was related to autophagic flux blockage. The phenomenon is confirmed by the results that M-PDT could induce autophagosomes accumulation and upregulate LC3-II and p62 expression. M-PDT elevated co-localization of RFP and GFP tandem-tagged LC3B puncta in cSCC cell, reflecting autophagic flux blockage, and this was confirmed by TEM. Furthermore, we noticed that M-PDT induced accumulated autophagosomes-dependent apoptosis via targeting ROS-mediated Akt/mTOR signaling. Suppression of Akt potentiated M-PDT-induced upregulation of LC3-II and p62 levels, whereas Akt activation and ROS inhibition rendered resistance to these events. In addition, we observed that lysosomal dysfunction was involved in M-PDT-triggered accumulated autophagosomes-dependent cSCC apoptosis. Conclusion: Our data demonstrates that M-PDT inhibits cSCC through blocking Akt/mTOR-mediated autophagic flux.